2013
DOI: 10.1371/journal.pone.0058191
|View full text |Cite
|
Sign up to set email alerts
|

Limited Anti-Inflammatory Role for Interleukin-1 Receptor Like 1 (ST2) in the Host Response to Murine Postinfluenza Pneumococcal Pneumonia

Abstract: Interleukin-1 receptor like 1 (ST2) is a negative regulator of Toll-like receptor (TLR) signaling. TLRs are important for host defense during respiratory tract infections by both influenza and Streptococcus (S.) pneumoniae. Enhanced susceptibility to pneumococcal pneumonia is an important complication following influenza virus infection. We here sought to determine the role of ST2 in primary influenza A infection and secondary pneumococcal pneumonia. ST2 knockout (st2 −/−) and wild-type (WT) mice were intranas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 58 publications
(83 reference statements)
0
10
0
Order By: Relevance
“…Finally, a role for type 2 innate lymphoid cells (ILC2) in superinfection has recently been demonstrated. ILC2 cells express the IL-33 receptor ST2 (interleukin-1 receptor-like 1), and ST2 Ϫ/Ϫ mice had higher S. pneumoniae burden and increased inflammation compared to WT animals during superinfection (48). These data suggest that ILC2 may play a protective role, perhaps by producing IL-13, during postinfluenza bacterial superinfection.…”
Section: Effects Of Influenza On T Cell-mediated Immunitymentioning
confidence: 85%
“…Finally, a role for type 2 innate lymphoid cells (ILC2) in superinfection has recently been demonstrated. ILC2 cells express the IL-33 receptor ST2 (interleukin-1 receptor-like 1), and ST2 Ϫ/Ϫ mice had higher S. pneumoniae burden and increased inflammation compared to WT animals during superinfection (48). These data suggest that ILC2 may play a protective role, perhaps by producing IL-13, during postinfluenza bacterial superinfection.…”
Section: Effects Of Influenza On T Cell-mediated Immunitymentioning
confidence: 85%
“…Similarly, tlr9-/- mice displayed accelerated growth of pneumococci upon infection of the lower airways together with enhanced mortality [13], while il-1rI-/- [29] and il-18-/- [30] mice showed a more modestly impaired immune response only reflected by higher bacterial loads. To our knowledge, the role of TLR7 has not been studied in the context of pneumococcal infections, while our laboratory recently showed that ST2 does not contribute to the host defense during S. pneumoniae pneumonia [26]. Together these data suggest that SIGIRR may impair the host defense during pneumococcal pneumonia via inhibition of TLR4, TLR9, IL-1RI, and/or IL-18R.…”
Section: Discussionmentioning
confidence: 99%
“…Lung histopathology was semiquantitatively analyzed as described [7,26]. In short: the ‘lung inflammation score' was expressed as the sum of 6 parameters [graded on a scale of 0 (absent) to 4 (severe)]: pleuritis, bronchitis, edema, interstitial inflammation, percentage of pneumonia, and endothelialitis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…60 Generally, a powerful and swift response to co-infection could reduce bacterial load and improve survival by preventing the need for a more aggressive, and often immunopathological response to control co-infection. 87 If, however, inflammation is insufficient for swift bacterial clearance, then the host might fare better to prioritise immune regulation over pathogen control while handing over the task of bacterial clearance to the adaptive immune response.…”
Section: Mechanismsmentioning
confidence: 99%